2021
DOI: 10.1093/cercor/bhab103
|View full text |Cite
|
Sign up to set email alerts
|

Global and Parallel Cortical Processing Based on Auditory Gamma Oscillatory Responses in Humans

Abstract: Gamma oscillations are physiological phenomena that reflect perception and cognition, and involve parvalbumin-positive γ-aminobutyric acid-ergic interneuron function. The auditory steady-state response (ASSR) is the most robust index for gamma oscillations, and it is impaired in patients with neuropsychiatric disorders such as schizophrenia and autism. Although ASSR reduction is known to vary in terms of frequency and time, the neural mechanisms are poorly understood. We obtained high-density electrocorticogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 78 publications
2
39
1
Order By: Relevance
“…ASSR power averaged across all electrodes showed a sustained response throughout the sound duration (Figure 3a, left panel). Focusing on brain responses to low sounds (30–60 Hz) across all participants (both groups together), we observed that ASSR power in this range was maximal in central and anterior contacts, a topographical pattern that is compatible with the recruitment of auditory and frontal regions as observed in intracranial recordings in humans (5, 18) and murine models (20).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…ASSR power averaged across all electrodes showed a sustained response throughout the sound duration (Figure 3a, left panel). Focusing on brain responses to low sounds (30–60 Hz) across all participants (both groups together), we observed that ASSR power in this range was maximal in central and anterior contacts, a topographical pattern that is compatible with the recruitment of auditory and frontal regions as observed in intracranial recordings in humans (5, 18) and murine models (20).…”
Section: Resultssupporting
confidence: 67%
“…When studying the neurophysiological origin of the non-linear pattern of aversion across frequencies using intracranial recordings in epileptic patients, we recently suggested that unlike aversion to higher frequencies in the pitch range (>130 Hz), aversion to rough frequencies is best accounted for by the sustained entrainment of activity of brain regions involved in salience and aversion processing (5). In other words, beyond triggering classical onset related potentials (ERPs) in the auditory cortex, the nonlinear effect of subjective aversion in the roughness range is arguably induced by the additional steadystate neural entrainment (ASSR) of widespread non-canonical auditory networks (5,17,18). Considering the disparity of aversion profiles between participants, we then hypothesized that one possible origin of this inter-individual variability might be the relative excitability of these networks and related ASSR responses across participants.…”
Section: Aversion To Roughness Links To Steady-state Excitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…We took advantage of auditory entrainment of gamma synchronization over parts of the cortical surface in the temporal and frontal lobes to replicate and expand previous evidence that variations in cortical cell density are involved in the generation of gamma synchrony in widespread cortical regions ( Fig. 3 ) ( Farahani et al., 2021 ; Koshiyama et al., 2020 ; Pellegrino et al., 2019b ; Tada et al., 2021 ).…”
Section: Discussionmentioning
confidence: 89%
“…Yet, recent evidence suggests that auditory-driven gamma synchronization rather involves the entire cortical mantle. This is supported by whole head EEG and MEG mapping ( Farahani et al., 2021 ; Pellegrino et al., 2019b ), invasive recordings in animal studies ( Cho et al., 2015 , 2020 ) and electrocorticography in epilepsy patients ( Tada et al., 2021 ). As such, exposure to gamma sounds provides a viable way to investigate gamma synchronization of the entire cortical surface.…”
Section: Introductionmentioning
confidence: 94%